Social Scoring and Emotion Recognition Systems in Family and Care Law Cases in the Context of Polish and European Law - Wilk, Anna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The article addresses the legal aspects of using some artificial intelligence tools in the broadly understood area of family law. These tools include social scoring systems, assessment of the risk of committing a crime and emotion recognition. They can be useful, for example, in the process of psychological assessment, analysis of data on the personal and property situation of specific persons in alimony proceedings, adoption or foster care, as well as in medically assisted procreation procedures. However, the use of these technologies involves a significant risk, which the legislator should counteract. The author therefore analyses whether the regulations adopted by the national and Community legislator are sufficient to eliminate this risk.